Genomic insights into the expansion of meropenem-resistant GPSC1-CC320 Streptococcus pneumoniae serotype 19A isolates from children under 5 years of age with invasive infections, 2018–2024 - Jin Lee; Jungsun Park; Tae-Min La; Ji-Yeon Hyeon; Hwanhee Kim; Seo Yeon Ko; Dong Hyeok Kim; Jaeil Yoo; Junyoung Kim (PLoS ONE, 2025)
The global rise of multidrug-resistant (MDR) Streptococcus pneumoniae serotype 19A despite widespread pneumococcal conjugate vaccine (PCV) use poses an emerging challenge for pediatric infectious disease control. In South Korea, the detection of serotype 19A initially declined following PCV13 implementation, but it has recently re-emerged, raising concerns over the evolution and persistence of high-risk clones. We investigated invasive serotype 19A isolates recovered from children under five years of age between 2018 and 2024. Antimicrobial susceptibility testing and whole-genome sequencing (WGS) were conducted to characterize resistance mechanisms, clonal structure, and phylogenetic relationships. Among the 104 invasive pneumococcal isolates, 11 (10.6%) were identified as serotype 19A. All of these belonged to GPSC1/CC320 and were classified as ST320 or ST6400. These isolates exhibited resistance to meropenem but retained susceptibility to cefotaxime, carrying a conserved pbp1a-13, pbp2b-11, and pbp2x-16 combination. Phylogenetic analysis revealed four distinct subclades among the South Korean isolates, each showing high similarity to international strains. To our knowledge, this is the first genomic study of meropenem-resistant 19A in children from South Korea. Our findings suggest that the resurgence of 19A is driven by stable, high-risk MDR. These results underscore the need for clone-level genomic surveillance to preempt emerging threats and inform next-generation vaccine and antibiotic strategies.